2013
DOI: 10.1080/01694243.2013.827095
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different light-curing modes on microleakage of posterior resin composites

Abstract: This investigation evaluated the effect of various curing modes on the extent of microleakage of differently resin-based posterior composites. Box-form Class II (MO/OD) cavities (n = 8) were prepared on proximal sides of 36 human sound mandibular molars. The cavities were restored by posterior composites (Filtek™ P90, Filtek™ Z250, and Filtek™ P60). The composite was placed in horizontal layers and irradiated occlusally by Astralis™ 10 light source at three modes of continuous intensities (conventional, high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Some scholars believe that the soft-start mode cannot reduce polymerization stress and microleakage, and that it has no significant effect on improving marginal adaptation in the bonding interface and degree of conversion of the resin monomer (Bouschlicher et al, 2000;Fleming et al, 2007). Too high or too low initial intensity cannot achieve a good curing effect (Marghalani, 2014), so the initial light intensity of the soft-start mode in our experiment is 400 mW/cm². Cunha et al (2007) reported that the soft-start mode did not reduce the degree of conversion, but led to lower shrinkage stress and higher bond strength, which demonstrated the correlation with shrinkage stress and bond strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars believe that the soft-start mode cannot reduce polymerization stress and microleakage, and that it has no significant effect on improving marginal adaptation in the bonding interface and degree of conversion of the resin monomer (Bouschlicher et al, 2000;Fleming et al, 2007). Too high or too low initial intensity cannot achieve a good curing effect (Marghalani, 2014), so the initial light intensity of the soft-start mode in our experiment is 400 mW/cm². Cunha et al (2007) reported that the soft-start mode did not reduce the degree of conversion, but led to lower shrinkage stress and higher bond strength, which demonstrated the correlation with shrinkage stress and bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…If shrinkage stress during the polymerization process is greater than the adhesive force in the bonding interface, it will generate gaps in the bonding interface and the material inside. Thus, the polymerization shrinkage of a composite resin has a lot of negative effects on clinical applications, such as microleakage, edge color, fracture of teeth or restorative materials, post-operative sensitivity, and secondary caries (Bouschlicher et al, 2000;Marghalani, 2014). To facilitate clinical operation and shorten treatment time, high-powered light-emitting diode (LED) light units came into being.…”
Section: Introductionmentioning
confidence: 99%